Nanosized Magnesium Electrochemically Deposited on a Carbon Nanotubes Suspension: Synthesis and Hydrogen Storage - Shen, Chaoqi; Aguey-Zinsou, Kondo-Francois (Frontiers in Energy Research, 2017)
Herein, we report on a novel method for deposition of Mg nanoparticles at the surface of carbon materials. Through the suspension of carbon nanotubes (CNTs) in an electrolyte containing di-n-butylmagnesium as a precursor, Mg nanoparticles were effectively deposited at the surface of the CNTs as soon as these touched the working electrode. Through this process CNTs supported Mg particles as small as 1 nm were synthesised and the distribution of the nanoparticles was found to be influenced by the concentration of the CNTs in the electrolyte. Hydrogenation of these nanoparticles at 100C was found to lead to low temperature hydrogen release starting at 150C, owing to shorter diffusion paths and higher hydrogen mobility in small Mg particles. However, these hydrogen properties drastically degraded as soon as the hydrogenation temperature exceeded 200C and this may be related to the low melting temperature of ultrasmall Mg particles.